Sistem Pemidanaan Tindak Pidana Narkotika dalam Perspektif Hukum Pidana Nasional - Azisa, Nur; Adhyanti Mirzana, Hijrah; Saddam Rivanie, Syarif; Munandar, M. Aris; Hamdani Ramli, Rafika Nurul (UNES Law Review, 2024)
This research uses normative legal research methods with a focus on analyzing legal norms. This research aims to reveal the basic aspects of the formation of certain laws, by analyzing related laws using a statute approach. The sentencing system in Law Number 1 Year 2023 on the Criminal Code (National Criminal Code) presents significant changes, especially in special criminal offenses such as narcotics. The sentencing guidelines introduced in the National Criminal Code allow for broader considerations in imposing punishment, taking into account aspects of justice and humanity. The death penalty is regulated with leniency, giving judges a lot of consideration before making a decision. For drug offenders, the National Criminal Code provides rehabilitation sanctions, showing a more humane approach. Drug sentencing under the National Criminal Code reflects an integrative sentencing theory, which combines the principle of retribution with considerations of crime prevention and offender rehabilitation. This marks a change in the Indonesian criminal law system that prioritizes justice and humanity.